The Challenges Associated With Connectivity in Ecosystem Processes - Hillman, Jenny R.; Lundquist, Carolyn J.; Thrush, Simon F. (Frontiers in Marine Science, 2018)
Developing a framework to quantify the transformation, sequestration or connectivity of energy and matter across habitats is one of the most significant challenges faced by ecologists and resource managers today. However, there are significant challenges associated with quantifying the ecosystem processes that connect and interact across habitats. These processes include the movement of nutrients and energy and can have substantial effects on the structure and dynamics of adjacent habitats and ecosystem functioning. Here, we use a connectivity framework developed for populations to inform our understanding of the challenges associated with connectivity in ecosystem processes, and how specific habitats can contribute to overall ecosystem functioning. The landscape patterns and potential connections between habitats in terms of material storage or transformation have important implications for understanding how fragmentation and degradation of habitats in ecosystems will influence broad-scale ecosystem function.